2019
DOI: 10.1175/jamc-d-18-0224.1
|View full text |Cite
|
Sign up to set email alerts
|

The Empirical Dependence of Tornadogenesis on Elevation Roughness: Historical Record Analysis Using Bayes’s Law in Arkansas

Abstract: Recent research suggests that surface elevation variability may influence tornado activity, though separating this effect from reporting biases is difficult to do in observations. Here we employ Bayes’s law to calculate the empirical joint dependence of tornado probability on population density and elevation roughness in the vicinity of Arkansas for the period 1955–2015. This approach is based purely on data, exploits elevation and population information explicitly in the vicinity of each tornado, and enables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…As observed in GD, terrain may have an important impact on the differences in tornado activities between the United States and China. Previous statistical analyses over the Great Plains and Arkansas have shown that terrain roughness has a negative effect on the tornado probability at a fixed population density (Jagger et al ., 2015; Elsner et al ., 2016; Hua and Chavas, 2019). China has fairly mountainous regions in the south, from Guangdong to Zhejiang Provinces.…”
Section: Discussionmentioning
confidence: 99%
“…As observed in GD, terrain may have an important impact on the differences in tornado activities between the United States and China. Previous statistical analyses over the Great Plains and Arkansas have shown that terrain roughness has a negative effect on the tornado probability at a fixed population density (Jagger et al ., 2015; Elsner et al ., 2016; Hua and Chavas, 2019). China has fairly mountainous regions in the south, from Guangdong to Zhejiang Provinces.…”
Section: Discussionmentioning
confidence: 99%
“…Rev.). Furthermore, topography and the frictional properties of the land cover have been proven to affect the vortex's intensity and physical structure (Lewellen 2012(Lewellen , 2014, and they may influence its genesis (Kellner and Niyogi 2014;Schenkman et al 2014;Roberts et al 2016;Lyza and Knupp 2018;Hua and Chavas 2019). Recent numerical simulations have provided additional support of these relationships (e.g., Coffer and Parker 2017;Dahl et al 2017;Fiedler 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the foundation provided by early laboratory simulations and recent numerical simulations, to date, there have been no peer-reviewed observational studies quantitatively investigating how the intensity of a tornado may be affected by topography or surface friction. Although some work has been devoted to examining the relationships between tornado behavior (genesis/decay, structure, path, and intensity) and surface topography, many of these studies have been idealized in some manner, and those that are observational [except Lyza and Knupp (2018) and Hua and Chavas (2019)] only analyzed a small number of cases or a singular event. Multiple observational studies have investigated ties between tornadogenesis and surface roughness 1 (e.g., Lamb 1957;Hardy 1971;Fujita 1973;Snider 1977;Elsom and Meaden 1982;Kellner and Niyogi 2014) but most of these studies suffer from spatiotemporal deficiencies, and, furthermore, their results have also been conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to gradients in atmospheric properties, supercells have also been found to be influenced by variability in land surface characteristics, particularly terrain [14][15][16][17]. Some studies have also noted that tornado development in supercells may be impacted by elevation changes [18][19][20][21][22] while others have explored the link between tornado formation and variations in surface roughness [22][23][24]. Numerical simulations have also shown that the development of near-ground rotation is sensitive to surface friction magnitude [25][26][27].…”
Section: Introductionmentioning
confidence: 99%